The Oticon Medical Neuro Zti cochlear implant and the Neuro 2 sound processor: multicentric evaluation of outcomes in adults and children. (1st February 2020) - Franco-Vidal, Valérie; Parietti-Winkler, Cécile; Guevara, Nicolas; Truy, Eric; Loundon, Natalie; Bailleux, Sonanda; Ardoint, Marine; Saaï, Sonia; Hoen, Michel; Laplante-Lévesque, Ariane; Mosnier, Isabelle; Bordure, Philippe; et al.
Abstract: Objective: This study evaluated the outcomes of the Oticon Medical Neuro Zti cochlear implant and the Neuro 2 sound processor. Design: Neuro One users were upgraded to Neuro 2. Monosyllabic word identification was evaluated in adults with Neuro One after ≥5 months, with Neuro 2 at upgrade, and with Neuro 2 after 3 months. Self-reported listening ability, satisfaction, and usability were measured in adults and children. Study sample: Participants were 44 adults and 26 children. Results: Speech identification scores in quiet and noise were 58% and 45% with Neuro One and 67% and 55% with Neuro 2 after 3 months, respectively. Hearing impairment duration and number of active electrodes significantly predicted speech identification in noise with Neuro 2. Significantly higher questionnaire ratings were obtained for Neuro 2 than Neuro One regarding listening ability in complex listening situations, comfort and music, as well as nine aspects of satisfaction and usability. Conclusion: This study demonstrates the clinical superiority of the Neuro 2 sound processor over Neuro One in terms of speech identification in quiet and in noise and reported patient benefit and satisfaction. Given the study design, sources of improvement may include factors unrelated to the sound processor itself.